Au-NP-based colorimetric assay for sugar detection and quantification - Mawin JM Jimenez; Andres Jaramillo-Botero; Alba Avila (Sensors and Actuators Reports, 2023)
Sugars have been associated with health problems such as metabolic syndrome, obesity, elevated triglycerides, and other features of metabolic disorders. Here, we report on the design and characterization of a highly sensitive gold nanoparticle (AuNP)-based assay for measuring sugars levels in fluids. AuNPs are functionalized with 4-mercaptobenzoic acid (4MBA) to modulate surface plasmonic resonance (SPR) frequency and fluorescent energy absorption by AuNPs, based on a fixed concentration of fluorescein introduced along with a fluid sample containing a determined quantity of sugar. We find the driving mechanism to be kinetic competition between fluorescein and saccharide which occupies the active carboxylic sites of the functional groups on the nanoparticle surface. This drives a colorimetric response in the 4MBA-AuNP solution, from orange to green, discernible to the naked eye. The aggregation of functionalized AuNPs as a result of increasing sugar concentration was confirmed via UV–vis spectroscopy and identified by a spectral peak of 620–675 nm. The limit of detection (LOD) was (55.8 ± 1.1) µM, with a highly repeatable calibration curve in the range of 0.09 – 2.45 mM. The assay's cost-effectiveness, speed, and simplicity open the door to multiple applications associated with detecting and quantifying sugars, including food science. The sensory platform was successfully tested in mixed sugar solutions to study the sensitivity capacity and applied to strawberry and kiwi freeze-dried samples. The results are validated by HPLC with refractive index detection.